IMPROVING STUDENTS’ READING COMPREHENSION BY USING CLASSWIDE PEER TUTORING (CWPT) METHOD (A Classroom Action Research to the Tenth Grade Students of SMKN 6 Pontianak in the Academic Year of 2019/2020) - Yana Susanti; Desi Sri Astuti; Yulia Ramadhiyanti (XXXX-XXXX, 2020)
This research was conducted to investigate how to improve students' reading comprehension after being taught using the Classwide peer tutoring (CWPT) method of tenth grade students of SMKN 6 Pontianak in the academic year 2019/2020. The form of this research is Classroom Action Research (CAR). The subjects of this study were 33 tenth grade students. Data collection techniques used were observation and measurement techniques. Observation sheets, field notes and reading tests were used as tools to collect data. Based on research findings, it showed that Classwide Peer Tutoring (CWPT) method can improve students' reading comprehension. Classwide Peer Tutoring (CWPT) method of successfully solving students' problems in reading. That is evident from the increase in student behavior and student grades. The students were shown by a significant increase in student scores which proved the improvement from the first cycle got an average score of 46.5. The score has not yet reached the average score, but after the researcher made improvement in the second cycle, the score increased to 70. This can be seen from the condition and behavior of students in teaching and learning and interested students are also introduced by using the Classwide Peer Tutoring (CWPT) method. Finally, the researcher concluded that students liked the Classwide Peer Tutoring (CWPT) method. This method can help students to improve students' reading comprehension by providing situations and ideas. Therefore, teachers need to use this method in class to improve students' reading comprehension in English. Keywords: Class Wide Peer Tutoring (CWPT) Method, Reading Comprehension